Characterization of the epidemiological profile of drug poisoning in the states of Piauí and Maranhão, peridual 2018-2020 (Research, Society and Development, 2020)
Exogenous intoxications represent a major public health problem and affect about 1.5% to 3% of the world population annually. These intoxications are due to the contact of the organism with potentially toxic substances, with drugs being one of the main agents related to the development of intoxications and, they can present distinct profiles of involvement that varied according to geographical, social, economic and cultural aspects. In view of this, this epidemiological and descriptive study aimed to trace the epidemiological profile of cases of poisoning reported in the states of Piauí and Maranhão in the period from 2018 to June 2020, through the survey of secondary data available at the Department of Informatics of the Unified System (DATASUS), based on the Information System for Notifiable Diseases (SINAN), applying variables such as: year of notification, sex, age and circumstance of intoxication. During the study period, 3465 cases of drug poisoning were identified. Among the states, Piauí had the highest number of cases, with 2318 of the cases, approximately 67%. In addition, the study demonstrated a significant increase in the number of cases over the years. Regarding the sociodemographic characteristics of the cases of intoxication, there was a higher frequency of involvement in female individuals (72.6%), aged 20-39 years (38.8%). Among the circumstances of intoxications, suicide attempt was predominant (55.73%), followed by therapeutic use (13.4%), accidental use (9.4%) and self-medication (7.4%). Thus, there is a need for health professionals to provide information about the correct use of medicines, especially pharmaceutical professionals, since they are responsible for ensuring the safe and effective use of medicines.